Relationship between brachycephalic airway syndrome and gastrointestinal signs in three breeds of dog. (9th August 2018) - Kaye, B. M.; Rutherford, L.; Perridge, D. J.; Ter Haar, G.
Abstract : Objectives: To assess the breed‐specific prevalence of, and effects of corrective airway surgery on, gastrointestinal signs in French bulldogs, English bulldogs and pugs presenting with brachycephalic airway syndrome to a referral teaching hospital. Materials and Methods: In this retrospective study, ptyalism, regurgitation and vomiting were graded at presentation using a previously established scoring system. Staphylectomy and nares resection were performed on all dogs. Gastrointestinal signs were re‐assessed via telephone follow‐up at least 6 weeks after surgery. Results: Ninety‐eight dogs were included: French bulldogs (n=43), English bulldogs (n=12) and pugs (n=43). Overall population prevalence of all gastrointestinal signs was 56%. Breed‐specific prevalence for French bulldogs was 93%, English bulldogs 58% and pugs 16%. There was post‐surgical clinical improvement in gastrointestinal signs for the whole study population, especially in French bulldogs. Clinical Significance: The prevalence of gastrointestinal signs in dogs presenting with brachycephalic airway syndrome and improvement in these clinical signs following corrective surgery may vary between breeds.